Technoeconomic analysis of a steam generation system with carbon capture - Giugliano, Luke, author; Bandhauer, Todd M., advisor; Jathar, Shantanu, committee member; Tong, Tiezheng, committee member (Colorado State University. Libraries, 2019)
Industrial steam generation consumes large amounts of natural gas (NG) and contributes significantly to CO2 emissions. Existing boiler technology is relatively inefficient, and its continued adoption could potentially be hampered by carbon emissions taxes due to the difficulty in CO2 separation from the dilute exhaust gas stream. This paper presents an alternative approach to steam generation that combines a membrane reactor (MR) to produce hydrogen from steam methane reforming (SMR), resulting in a concentrated CO2 exhaust. The performance of the system is evaluated using a coupled thermodynamic and technoeconomic analysis of an industrial-scale SMR plant to produce hydrogen in a MR used primarily for the purpose of steam generation (SG). The proposed SMR-MR-SG system converts NG to clean-burning hydrogen (H2), burns H2 to generate steam, and captures and concentrates CO2. Unused NG and H2 are recycled back into the system with uncaptured CO2 to increase efficiency. The SMR-MR-SG is compared to two baseline systems: a natural gas industrial boiler system (BS), and the same boiler system with integrated CO2 capture (BSC). The SMR-MR-SG improves on the BS by increasing efficiency from 86% to 97% and reducing NG and water consumption by 14% and 55%, respectively. Additionally, the SMR-MR-SG uses cryogenic separation and gas recycling to completely eliminate CO2 emissions with a 3.0% energy penalty, much less than comparable systems with carbon capture. The SMR-MR-SG has a capital cost about three times the BS and twice the BSC, but makes up for it quickly with reducing operating costs. Using a conservative prediction of carbon tax, the SMR-MR-SG has a payback period of 1.86 and 1.26 years and a discounted lifetime cost reduction of 42% and 43% relative to the BS and BSC, respectively. A sensitivity analysis showed that the results are most heavily influenced by the amount of carbon tax implemented in the future, with no carbon tax corresponding to a payback period of 8.05 years relative to the BS. The results of this modelling study show that the SMR-MR-SG could be a direct replacement for common industrial boiler systems as a new, efficient, and clean steam generation system.
Keywords: membrane; reactor; steam; methane; generation; reforming